Mislocated extrauterine intrauterine devices: Diagnosis and surgical management - Kaplanoğlu, Mustafa (J Turk Ger Gynecol Assoc, 2015)
OBJECTIVE: Presentation of the diagnostic and surgical treatment methods of our extrauterine intrauterine device (IUD) cases. MATERIAL AND METHODS: We retrospectively evaluated the data of 21 extrauterine IUD cases at our clinic between 2008 and 2010. The symptoms, diagnostic methods, and surgical treatments were evaluated. RESULTS: A total of 14 copper and seven levonorgestrel (LNG) IUDs were used. IUD had been inserted during lactation in 71.4% of the patients. The reasons for presentation of patients were unintended pregnancy in 19.05%, pelvic pain in 19.05%, and pelvic pain with vaginal bleeding in 23.8%. IUD in two patients were located the retroperitoneal area. IUD string had not been visible during routine follow-up in 38.1% of the patients. Laparoscopy was performed in 14 patients and laparotomy was performed for dense adhesions in seven patients. CONCLUSION: Extrauterine IUDs can present with various clinical symptoms. Ultrasonography and X-Ray are sufficient for the diagnosis. Surgical removal is needed to prevent possible complications, and the preferred surgical technique in appropriate patients is laparoscopy.